Detection of the characters from the license plates by cascade classifiers method - Quezada Sarmiento, P. (2016)
this article describes the detection of the characters of the license plate through of computer vision techniques such as cascade of classifiers based in Sobel algorithm, analysis of peaks, and valleys and learning vector machines; the search for the region of the plate begins by detecting vehicles, then, character segmentation and concludes with the recognition of these. The system it was tested in different scenarios: such as different lighting provided by the day or night, and weather changes. The average time to execute these phases it was 434 ms.